Human structural plasticity at record speed. - Johansen-Berg, H; Baptista, C; Thomas, A (2012)
How rapidly does learning shape our brains? A new study in this issue of Neuron by Sagi et al. (2012) that uses diffusion magnetic resonance imaging in both humans and rats suggests that just 2 hr of spatial learning is sufficient to change brain structure.